Fluid Overload in Critically Ill Children - Raina, Rupesh; Sethi, Sidharth Kumar; Wadhwani, Nikita; Vemuganti, Meghana; Krishnappa, Vinod; Bansal, Shyam B. (Frontiers in Pediatrics, 2018)
Abstract Background: A common practice in the management of critically ill patients is fluid resuscitation. An excessive administration of fluids can lead to an imbalance in fluid homeostasis and cause fluid overload (FO). In pediatric critical care patients, FO can lead to a multitude of adverse effects and increased risk of morbidity. Objectives: To review the literature highlighting impact of FO on a multitude of outcomes in critically-ill children, causative versus associative relationship of FO with critical illness and current pediatric fluid management guidelines. Data Sources: A literature search was conducted using PubMed/Medline and Embase databases from the earliest available date until June 2017. Data Extraction: Two authors independently reviewed the titles and abstracts of all articles which were assessed for inclusion. The manuscripts of studies deemed relevant to the objectives of this review were then retrieved and associated reference lists hand-searched. Data Synthesis: Articles were segregated into various categories namely pathophysiology and sequelae of fluid overload, assessment techniques, epidemiology and fluid management. Each author reviewed the selected articles in categories assigned to them. All authors participated in the final review process. Conclusions: Recent evidence has purported a relationship between mortality and FO, which can be validated by prospective RCTs (randomized controlled trials). The current literature demonstrates that ‘clinically significant’ degree of FO could be below 10%. The lack of a standardized method to assess FB (fluid balance) and a universal definition of FO are issues that need to be addressed. To date, the impact of early goal directed therapy and utility of hemodynamic parameters in predicting fluid responsiveness remains underexplored in pediatric resuscitation.